2013
DOI: 10.2319/021413-133.1
|View full text |Cite
|
Sign up to set email alerts
|

Does proclination of maxillary incisors really affect the sagittal position of point A?

Abstract: Objective: To examine the effect of maxillary incisor proclination due to orthodontic treatment upon the sagittal position of point A and evaluate the effect of this possible movement of point A on sella-nasion-point A (SNA) angle. Materials and Methods: A study group was formed from 25 subjects (12 male and 13 female) who had Class II division 2 malocclusion with retroclined upper incisors, and a control group was formed from 25 subjects (12 male and 13 female) who had minor crowding in the beginning of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…[8][9][10] Few studies also attempted to find the effect of torquing of incisors on position of point A. 4,6,[11][12][13] But only very few investigators tried to establish a direct association between the degrees of changes in the inclination of incisor to movement of point A. 2 With this background in this study, we made an attempt to determine the relation between the degree of incisor inclination correction and anteroposterior movement of point A by studying pre-and postalignment lateral cephalograms of class II division 2 and in class III patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Few studies also attempted to find the effect of torquing of incisors on position of point A. 4,6,[11][12][13] But only very few investigators tried to establish a direct association between the degrees of changes in the inclination of incisor to movement of point A. 2 With this background in this study, we made an attempt to determine the relation between the degree of incisor inclination correction and anteroposterior movement of point A by studying pre-and postalignment lateral cephalograms of class II division 2 and in class III patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 This is especially so in the case of palatal torque done in class II division 2. Another observed fact is that the center of rotation is located close to bracket irrespective of type of torque.…”
Section: Wjdmentioning
confidence: 99%
“…A few studies have attempted to investigate the effect of incisor inclination on the position of points A and B. Erverdi [12] showed a direct correlation between incisor inclination changes and point A. Hassan et al [13]found that if the upper incisor is retroclined by 10°, point A will move superiorly by 0.6 mm. In another study by Bicakci et al [14], it was found that the proclination of the maxillary incisors along with the backward movement of the incisor root apex causes a change in the horizontal position of point A. It was suggested to use the linear movement of the incisor apex, rather than the angular measurements to evaluate the sagittal change of point A [14].…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Bicakci et al [14], it was found that the proclination of the maxillary incisors along with the backward movement of the incisor root apex causes a change in the horizontal position of point A. It was suggested to use the linear movement of the incisor apex, rather than the angular measurements to evaluate the sagittal change of point A [14]. Nevertheless, research on this topic has been limited thus far.…”
Section: Introductionmentioning
confidence: 99%
“…However the points are dento-alveolar and are considered unreliable as they are affected by surface remodelling and underlying tooth position. 4 Post-operative skeletal position should rely on basal bone assessment as any post-operative dental changes may camouflage the true basal bone position. Therefore clinical or 2D radiological assessment of teeth position may not accurately reflect basal bone changes.…”
Section: Introductionmentioning
confidence: 99%